Nickel-based alloy powder, cladding layer and preparation method of nickel-based alloy powder and cladding layer
Through the specific composition of nickel-based alloy powder and vacuum smelting atomization powdering process, the problems of uneven spherical shape and poor fluidity in laser cladding 3D printing are solved, and the cladding layer with high hardness and density are achieved, which improves the strength and wear resistance of the cladding layer.
Patent Information
- Application Number
- CN202510105243.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2025-05-02
AI Technical Summary
In laser cladding 3D printing, traditional nickel-based alloy metal powders have problems such as uneven spherical shape, poor fluidity, high oxygen content, uneven particle size distribution, and easy to lead to insufficient hardness of the cladding layer, prone to cracking and powder blocking, resulting in insufficient strength, wear resistance and corrosion resistance of the cladding layer.
A nickel-based alloy powder composed of Ni, W, B, Si, Cr, Nb, Co, La, and Hf with a specific content is prepared by vacuum smelting and atomizing powder making process to ensure that the powder has excellent fluidity, extremely low oxygen content, high spherical shape and uniform particle size distribution. It is used for laser cladding 3D printing to overcome the problems caused by high cladding rates.
The prepared nickel-based alloy powder can effectively avoid cold cracking and powder blocking problems, obtain a high-hardness cladding with good density and hardness in the 50HRC-55HRC range, and improve the strength, wear resistance and corrosion resistance of the cladding layer.
Smart Images

Figure BDA0005255315920000121 
Figure BDA0005255315920000131 
Figure HDA0005255316010000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of materials for laser cladding 3D printing, and in particular to a nickel-based alloy powder and a preparation method thereof, a cladding layer and a preparation method thereof. Background Art
[0002] From the perspective of industrial demand, in many fields such as machinery manufacturing, aerospace, energy and electricity, many parts have been operating under harsh conditions such as high temperature, high pressure, high speed, corrosion, etc. for a long time. Traditional surface treatment technologies, such as electroplating and thermal spraying, sometimes cannot meet high performance requirements. For example, on aircraft engine blades, a more reliable surface strengthening technology is needed to improve its high temperature resistance, wear resistance and corrosion resistance, and laser cladding technology came into being.
[0003] From the perspective of technological progress, the rapid development of laser technology is an important foundation for the emergence of laser cladding. The emergence and performance improvement of high-power lasers can provide enough energy to melt metal powder or substrate surface, and the laser energy can be precisely controlled, enabling precise cladding operations.
[0004] From the perspective of material science progress, various high-performance alloy powders, ceramic powders and other materials have been developed. These materials can be selected according to the specific needs of cladding, thus providing a diverse material basis for laser cladding technology, enabling it to achieve multiple functions, such as preparing wear-resistant coatings, corrosion-resistant coatings, etc.
[0005] Traditional nickel-based alloy metal powders generally have the following defects: too many needle-like objects, a large number of irregularly shaped powder particles, uneven sphericity, many rod-like structures, many satellite balls and hollow powders, obvious oxidized particles, visible inclusions, rough surface, low powder yield, etc. When traditional nickel-based alloy metal powders are used in laser cladding 3D printing technology, the hardness of the cladding layer is not enough. During the laser cladding process, the cladding layer is prone to cracking, powder blocking and other performance and process performance problems, resulting in low strength, insufficient wear resistance and corrosion resistance, and low service life of the cladding layer.
[0006] In summary, new nickel-based alloy powder and cladding layer technical solutions still need to be studied to obtain nickel-based alloy powder with high sphericity, good fluidity, uniform particle size distribution and low oxygen content, which can better meet the performance requirements of laser cladding 3D printing technology, overcome the chilling cracking and powder blocking problems caused by the high cladding rate in the existing technology, and obtain a cladding layer with good density (no pores, no impurities, dense structure, refined grains) and hardness that meets the requirements, thereby improving the strength, wear resistance, corrosion resistance and service life of the cladding layer. Summary of the invention
[0007] The purpose of the present invention is to provide a nickel-based alloy powder with extremely low oxygen content (≤80ppm), excellent fluidity (≤12s / 50g), high sphericity and uniform particle size distribution, which can well meet the performance requirements of laser cladding 3D printing technology, so as to overcome the chill cracking problem and powder blocking problem caused by the high cladding rate in the prior art, and obtain a high-hardness cladding layer with good density (no pores, no impurities, dense structure, and refined grains) and a hardness in the range of 50HRC-55HRC.
[0008] In order to achieve the above object, the present invention provides the following technical solutions.
[0009] In a first aspect, the present invention provides a nickel-based alloy powder, wherein, based on the total mass of the nickel-based alloy powder being 100%, the element composition of the nickel-based alloy powder comprises: 6-7% W, 4-8% B, 5-7% Si, 18-22% Cr, 2-3% Nb, 32-36% Co, 0.8-1.2% La, 1.5-2% Hf, ≤0.1% impurities and the balance Ni;
[0010] The nickel-based alloy powder has a particle size of 45-180 μm, fluidity ≤12s / 50g, microscopic particle sphericity ≥95%, oxygen content ≤80ppm, and bulk density ≥4.60g / cm 3 , tap density ≥5.30g / cm 3 .
[0011] The nickel-based alloy powder provided by the present invention is composed of specific contents of Ni, W, B, Si, Cr, Nb, Co, La, and Hf, and has excellent fluidity (≤12s / 50g, the fluidity of existing nickel-based alloy powder is generally not less than 15s / 50g), extremely low oxygen content (≤80ppm, the oxygen content of existing nickel-based alloy powder generally exceeds 100ppm, and very few are in the range of 90-100ppm), suitable powder particle size range, high sphericity, good loose density and tap density, and can well meet the performance requirements of laser cladding 3D printing technology. When used for laser cladding 3D printing, it can effectively avoid the chill cracking problem and powder blocking problem caused by high cladding rate, and obtain a cladding layer with good density (no pores, no impurities, dense structure, and refined grains) and a hardness between 50HRC and 55HRC.
[0012] The nickel-based alloy powder provided by the present invention is composed of Ni, W, B, Si, Cr, Nb, Co, La, and Hf in specific contents. Specifically:
[0013] Among them, the addition of an appropriate amount of W element in the alloy can produce a solid solution strengthening effect. It dissolves in the lattice of the base metal, causing lattice distortion and increasing the resistance to dislocation movement, thereby improving the strength and hardness of the alloy.
[0014] Among them, the addition of an appropriate amount of B element in the alloy can produce an effective effect of strengthening the grain boundaries. In the alloy, B is concentrated at the grain boundaries, which reduces the grain boundary energy, hinders the movement of the grain boundaries, and refines the grains, thereby improving the strength and toughness of the alloy; in addition, the addition of an appropriate amount of B element can significantly improve the hardenability of the alloy. B can make the alloy easier to form a martensitic structure during quenching, thereby increasing the hardness of the alloy.
[0015] Among them, the addition of an appropriate amount of Si element can effectively improve the hardness and strength of the cladding layer, enhance the wear resistance of the cladding layer, play a deoxidation role, and improve the mechanical properties and corrosion resistance of the material.
[0016] Among them, the addition of an appropriate amount of Cr element can improve the high-temperature oxidation resistance of the alloy. Under high-temperature conditions, the chromium oxide film generated by the reaction of Cr with oxygen can prevent further oxidation of the alloy. At the same time, Cr can also improve the thermal stability of the alloy. In high-temperature alloys, Cr can enable the alloy to maintain good mechanical properties at high temperatures.
[0017] Among them, the addition of an appropriate amount of Nb element in the alloy can produce a solid solution strengthening effect. Nb dissolves in the alloy matrix, causing lattice distortion and increasing the resistance to dislocation movement, thereby improving the strength of the alloy. In nickel-based alloys, this solid solution strengthening effect helps to improve the mechanical properties of the alloy. Nb helps to improve oxidation resistance. It can promote the formation of a denser oxide film on the surface of the alloy, which can enhance its oxidation resistance in high temperature environments. At the same time, Nb can also improve the corrosion resistance of the alloy to a certain extent. In some corrosive environments (such as seawater environments), Nb-containing alloys can better resist the erosion of corrosive media.
[0018] Among them, the addition of an appropriate amount of Co element in the alloy can produce a solid solution strengthening effect. Co dissolves in the lattice of the base metal, causing lattice distortion, thereby hindering dislocation movement and effectively increasing the strength and hardness of the alloy. The solid solution strengthening effect of Co helps the alloy maintain good mechanical properties under high temperature and high stress environments. Co can form compounds with some elements, and these compounds are dispersed in the alloy matrix in the form of fine particles, playing a role of dispersion strengthening.
[0019] Among them, the addition of an appropriate amount of La can play a role in deoxidation and desulfurization. Sulfur and oxygen are harmful elements, and La can react with them to form stable compounds, such as La2O3, La2S3, etc. These compounds can float up from the alloy liquid and be removed, thereby improving the purity of the alloy. It can refine the grain structure of the alloy, and the structure will become finer and more uniform, which helps to improve the mechanical properties of the alloy such as strength, hardness and toughness. In addition, La can also improve the oxidation resistance of the alloy. It can form a dense protective film on the surface of the alloy, preventing oxygen from further corroding the interior of the alloy and extending the service life of the alloy.
[0020] Among them, the addition of an appropriate amount of Hf element can strengthen the alloy matrix. It can be integrated into the nickel lattice through solid solution strengthening, produce lattice distortion, hinder dislocation movement, and thus effectively improve the strength and hardness of the alloy. After adding Hf, it can withstand higher stress, prevent the sliding of grain boundaries at high temperatures, and further improve the high temperature strength and creep resistance of the alloy.
[0021] Among them, the addition of an appropriate amount of Ni element can improve the wettability and ductility of the cladding layer. On the other hand, it can improve the corrosion resistance of the cladding layer. It has high corrosion resistance to acids and alkalis, which can effectively improve the corrosion resistance of the coating. It can also improve the corrosion resistance and plasticity of the laser cladding alloy for columns.
[0022] Among them, the mass percentage of other impurities in the nickel-based alloy powder is ≤0.1%, and the impurities mainly include P, S, H, Cu, Al, etc. The lower the mass percentage of impurity elements, the better the quality of the powder.
[0023] According to a preferred embodiment of the first aspect, preferably, the particle size distribution of the nickel-based alloy powder satisfies D10 (referring to the particle size value corresponding to when the cumulative particle size distribution percentage from small to large reaches 10%) of 40-50 um.
[0024] According to a preferred embodiment of the first aspect, preferably, the particle size distribution of the nickel-based alloy powder satisfies D50 (median particle size, which refers to the particle size value corresponding to when the cumulative particle size distribution percentage from small to large reaches 50%) of 110-120 um.
[0025] According to a preferred embodiment of the first aspect, preferably, the particle size distribution of the nickel-based alloy powder satisfies D90 (referring to the particle size value corresponding to when the cumulative particle size distribution percentage from small to large reaches 90%) of 170-180 um.
[0026] According to a preferred embodiment of the first aspect, preferably, based on the total mass of the nickel-based alloy powder being 100%, the mass content of the hollow powder in the nickel-based alloy powder does not exceed 1%.
[0027] In a second aspect, the present invention provides a method for preparing the nickel-based alloy powder provided in the first aspect of the present invention, wherein the method comprises:
[0028] According to the element composition of the nickel-based alloy powder, the raw materials of Ni, W, B, Si, Cr, Nb, Co, La and Hf are weighed and mixed;
[0029] All raw materials are subjected to vacuum melting and gas atomization powder making, and the nickel-based alloy powder is obtained after screening; wherein, during the vacuum melting and gas atomization powder making process, the vacuum degree of vacuum melting does not exceed 10Pa, the pressure of gas atomization is 4-6MPa, and vacuum melting and gas atomization are carried out under a protective gas atmosphere.
[0030] The technical solution provided by the present invention uses specific amounts of Ni, W, B, Si, Cr, Nb, Co, La, and Hf to mix and then perform vacuum melting gas atomization powder making under specific parameters and sieving, so as to prepare a powder with excellent fluidity (≤12s / 50g, the fluidity of existing nickel-based alloy powder is generally not less than 15s / 50g), extremely low oxygen content (≤80ppm, the oxygen content of existing nickel-based alloy powder is generally more than 100ppm, and very few are within the range of 90-100ppm), high sphericity (≥95%), appropriate powder particle size range (particle size 45-180μm, D10 is 40-50um, D50 is 110-120um, D90 is 170-180um), good bulk density and tap density (bulk density ≥4.60g / cm 3 , tap density ≥5.30g / cm 3 ), nickel-based alloy powder with no hollow powder, dry appearance, no obvious oxidation color particles, and high purity; and the powder yield rate of the particle size range of 45-180μm can reach more than 70%. The nickel-based alloy powder prepared by the technical solution provided by the present invention can well meet the technical performance requirements of laser cladding 3D printing. It can be used for laser cladding 3D printing to overcome the chilling cracking problem and powder blocking problem caused by high cladding rate, and obtain a high-hardness cladding layer with good density (no pores, no impurities, dense organization, and refined grains) and hardness in the range of 50HRC-55HRC.
[0031] According to a preferred embodiment of the second aspect, preferably, the Ni, W, B, Si, Cr, Nb, Co, La, and Hf raw materials are Ni metal, W metal, B element, Si element, Nb metal, Co metal, La metal, and Hf metal.
[0032] According to a preferred embodiment of the second aspect, preferably, vacuum melting and gas atomization powder making comprises the steps of charging, vacuuming, melting and atomizing performed in sequence.
[0033] According to a preferred embodiment of the second aspect, preferably, in the vacuum melting gas atomization powder making process, the vacuum melting atmosphere is an inert gas atmosphere.
[0034] According to a preferred embodiment of the second aspect, preferably, in the vacuum melting and gas atomization powder making process, the vacuum melting temperature is 1620-1690°C.
[0035] According to a preferred embodiment of the second aspect, preferably, in the vacuum melting gas atomization powder making process, the atomization medium gas is argon.
[0036] In a third aspect, the present invention provides a method for preparing a cladding layer, wherein the method comprises:
[0037] Using the nickel-based alloy powder provided by the first aspect of the present invention as a raw material, a cladding layer is prepared on the surface of a workpiece by a laser cladding 3D printing method;
[0038] Among them, the laser cladding parameters are: laser power 2300-2600W, spot diameter 0.8-1.2mm, scanning line speed 26-32m / min, vacuum degree of vacuum environment ≤0.1pa, powder feeding rate 32-38g / min;
[0039] Among them, the thickness of the cladding layer does not exceed 2mm.
[0040] The technical solution provided by the present invention utilizes specific nickel-based alloy powder in combination with certain laser cladding parameters to adopt laser cladding 3D printing technology to prepare the cladding layer, thereby overcoming the chill cracking problem and powder blocking problem caused by the high cladding rate in the prior art, and obtaining a high-hardness cladding layer with good density (no pores, no impurities, dense structure, and refined grains) and a hardness in the range of 50HRC-55HRC.
[0041] According to a preferred embodiment of the third aspect, preferably, the working gas used in laser cladding is argon.
[0042] According to a preferred embodiment of the third aspect, preferably, the thickness of the cladding layer is 1-2 mm.
[0043] According to a preferred embodiment of the third aspect, preferably, the surface of the workpiece is pretreated before the cladding layer is prepared to remove the oxide layer and stains on the surface of the workpiece.
[0044] According to a preferred embodiment of the third aspect, preferably, the nickel-based alloy powder is first sieved and dried before being used for preparing the cladding layer;
[0045] Further, the sieving is sequentially sieved through an 80-mesh sieve and a 325-mesh sieve to obtain a nickel-based alloy powder with a particle size of 45-180 μm;
[0046] Furthermore, drying is achieved by drying at 100-120° C. for 1-2 hours under a vacuum degree of ≤20 Pa.
[0047] In a fourth aspect, the present invention provides a cladding layer, which can be prepared by the preparation method of the cladding layer provided by the third aspect of the present invention, and the hardness of the cladding layer is 50HRC-55HRC.
[0048] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0049] 1. The nickel-based alloy powder provided by the technical solution of the present invention has a particle size distribution of 45-180 μm, a fluidity of ≤12 s / 50 g, a spherical or nearly spherical appearance, a microscopic particle sphericity of ≥95%, an oxygen content of ≤80 ppm, and a bulk density of ≥4.60 g / cm 3 , tap density ≥5.30g / cm 3 , improving the performance of powder in laser cladding 3D printing.
[0050] 2. The nickel-based alloy powder provided by the technical solution of the present invention can overcome the problems of insufficient wear resistance and corrosion resistance, chill cracking caused by high cladding rate, powder blockage and other performance and process performance of traditional nickel-based alloy metal powder when used in laser cladding 3D printing, thereby improving the hardness of the cladding layer.
[0051] 3. The vacuum melting gas atomization powder making process of the technical solution of the present invention is carried out under a protective gas atmosphere, which effectively isolates the contact between the alloy liquid and oxygen, avoids the oxidation of the powder, and further reduces the oxygen content of the nickel-based alloy powder.
[0052] 4. The nickel-based alloy powder provided by the technical solution of the present invention is used in laser cladding 3D printing to obtain a cladding layer with good density (no pores, no impurities, dense structure, and refined grains) and a hardness between 50HRC and 55HRC. The cladding layer has high hardness, low cost, and good metallurgical bonding with the base metallurgy, which can effectively improve the cladding efficiency.
[0053] 5. The nickel-based alloy powder prepared by the preparation method of the nickel-based alloy powder provided by the technical solution of the present invention has a particle size distribution of 45-180 μm, D10 of 40-50 um, D50 of 110-120 um, D90 of 170-180 um, and has no hollow powder, which is more conducive to cladding coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 This is a particle morphology diagram of the nickel-based alloy powder provided in Example 1.
[0055] Figure 2 This is a crystal image of the hollow powder of nickel-based alloy powder provided in Example 1.
[0056] Figure 3 This is a crystal image of the hollow powder of nickel-based alloy powder provided in Comparative Example 1. DETAILED DESCRIPTION
[0057] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.
[0058] Example 1
[0059] This embodiment provides a nickel-based alloy powder and a cladding layer.
[0060] The elemental composition of the nickel-based alloy powder provided in this embodiment includes (based on the total mass of the nickel-based alloy powder as 100%): 6.5% W, 5% B, 6% Si, 20% Cr, 2.5% Nb, 34% Co, 1% La, 1.8% Hf, 0.02% impurities and the remainder Ni.
[0061] The nickel-based alloy powder provided in this embodiment is prepared by the following method:
[0062] (1) According to the elemental composition of the nickel-based alloy powder, 22.3 kg of raw materials Ni metal, 6.6 kg of W metal, 5.1 kg of B element, 6.1 kg of Si element, 20.1 kg of Cr element, 2.6 kg of Nb metal, 34.2 kg of Co metal, 1.1 kg of La metal and 1.9 kg of Hf metal were weighed for mixing; wherein the purity of Ni metal was 99.99 wt%, the purity of W metal was 99.96 wt%, the purity of B element was 99.5 wt%, the purity of Si element was 99.58 wt%, the purity of Cr element was 99.2 wt%, the purity of Nb metal was 99.92 wt%, the purity of Co metal was 99.95 wt%, the purity of La metal was 96.8 wt%, and the purity of Hf metal was 98 wt%;
[0063] (2) All raw materials are subjected to vacuum melting and gas atomization powder making, and then sieved (passed through an 80-mesh sieve and a 325-mesh sieve in sequence) to obtain a powder with a particle size of 45-180 μm, which is the nickel-based alloy powder provided in this embodiment; wherein, during the vacuum melting and gas atomization powder making process, the vacuum degree of vacuum melting does not exceed 10 Pa, the vacuum melting atmosphere is an argon atmosphere, the vacuum melting temperature is 1651° C., the gas atomization pressure is 4.6 MPa, and the gas atomization medium gas is argon.
[0064] In the above preparation method, the yield of powder with a particle size range of 45-180 μm is 78.3%; the particle size distribution of the prepared nickel-based alloy powder satisfies: particle size of 45-180 μm, D10 of 45 μm, D50 of 112.1 μm, D90 of 173 μm, fluidity of about 11.2 s / 50 g, and microscopic particle sphericity of about 96.1% (such as Figure 1 As shown), oxygen content is about 65ppm, and bulk density is 4.67g / cm 3 , tap density 5.41g / cm 3 , no hollow noodles (such as Figure 2 shown).
[0065] The cladding layer provided in this embodiment is prepared by the following method:
[0066] (1) The nickel-based alloy powder provided in this embodiment was sieved (passed through an 80-mesh sieve and a 325-mesh sieve in sequence to obtain a nickel-based alloy powder with a particle size of 45-180 μm) and dried (dried at 110° C. for 1.5 h under a vacuum degree of 15 Pa) to obtain a pretreated nickel-based alloy powder;
[0067] (2) The oxide layer and stains on the surface of the target shaft workpiece are removed by lathe processing. The size of the target shaft workpiece is 50 mm in diameter and 100 mm in length. The cladding area of the target shaft workpiece is 0.253 m 2 ;
[0068] (3) using the pretreated nickel-based alloy powder obtained in step (1), and adopting a laser cladding 3D printing method to prepare a cladding layer on the surface of the target shaft workpiece treated in step (2);
[0069] Among them, the laser used in laser cladding 3D printing is a semiconductor laser, and the laser cladding process parameters are: laser power 2500W, spot diameter 1.0mm, scanning line speed 30m / min, vacuum degree of vacuum environment ≤0.1pa, powder feeding rate 35g / min, working gas is argon;
[0070] Among them, the coating thickness is 1.1mm;
[0071] (4) The target shaft workpiece obtained in step (3) is finally sandblasted on a machine tool according to the designed dimensions.
[0072] The performance data of the cladding layer of this embodiment are shown in Table 1.
[0073] Example 2
[0074] This embodiment provides a nickel-based alloy powder and a cladding layer.
[0075] The elemental composition of the nickel-based alloy powder provided in this embodiment includes (based on the total mass of the nickel-based alloy powder as 100%): 6.7% W, 5.5% B, 6.3% Si, 18.8% Cr, 2.7% Nb, 34.8% Co, 1.08% La, 1.88% Hf, 0.03% impurities and the remainder Ni.
[0076] The nickel-based alloy powder provided in this embodiment is prepared by the following method:
[0077] (1) According to the elemental composition of the nickel-based alloy powder, weigh 21.8 kg of raw materials Ni metal, 6.8 kg of W metal, 5.5 kg of B element, 6.4 kg of Si element, 18.9 kg of Cr element, 2.7 kg of Nb metal, 35 kg of Co metal, 1 kg of La metal and 1.9 kg of Hf metal for mixing; wherein the purity of Ni metal is 99.99 wt%, the purity of W metal is 99.96 wt%, the purity of B element is 99.5 wt%, the purity of Si element is 99.58 wt%, the purity of Cr element is 99.2 wt%, the purity of Nb metal is 99.92 wt%, the purity of Co metal is 99.95 wt%, the purity of La metal is 96.8 wt% and the purity of Hf metal is 98 wt%;
[0078] (2) All raw materials are subjected to vacuum melting and gas atomization powder making, and then sieved (passed through an 80-mesh sieve and a 325-mesh sieve in sequence) to obtain a powder with a particle size of 45-180 μm, which is the nickel-based alloy powder provided in this embodiment; wherein, during the vacuum melting and gas atomization powder making process, the vacuum degree of vacuum melting does not exceed 10 Pa, the atmosphere of vacuum melting is an argon atmosphere, the temperature of vacuum melting is 1646° C., the pressure of gas atomization is 4.8 MPa, and the medium gas of gas atomization is argon.
[0079] In the above preparation method, the yield of powder with a particle size range of 45-180 μm is 76.8%; the particle size distribution of the prepared nickel-based alloy powder satisfies: particle size of 45-180 μm, D10 of 45.9 μm, D50 of 116.3 μm, D90 of 175 μm, fluidity of about 11.4 s / 50 g, microscopic particle sphericity of about 96.2%, oxygen content of about 68 ppm, and bulk density of 4.63 g / cm 3 , tap density 5.43g / cm 3 , no hollow noodles.
[0080] The cladding layer provided in this embodiment is prepared by the following method:
[0081] (1) The nickel-based alloy powder provided in this embodiment was sieved (passed through an 80-mesh sieve and a 325-mesh sieve in sequence to obtain a nickel-based alloy powder with a particle size of 45-180 μm) and dried (dried at 115° C. for 1.8 h under a vacuum degree of 14 Pa) to obtain a pretreated nickel-based alloy powder;
[0082] (2) The oxide layer and stains on the surface of the target shaft workpiece are removed by lathe processing. The size of the target shaft workpiece is 50 mm in diameter and 100 mm in length. The cladding area of the target shaft workpiece is 0.253 m 2 ;
[0083] (3) using the pretreated nickel-based alloy powder obtained in step (1), and adopting a laser cladding 3D printing method to prepare a cladding layer on the surface of the target shaft workpiece treated in step (2);
[0084] Among them, the laser used in laser cladding 3D printing is a semiconductor laser, and the laser cladding process parameters are: laser power 2500W, spot diameter 1.0mm, scanning line speed 30m / min, vacuum degree of vacuum environment ≤0.1pa, powder feeding rate 35g / min, working gas is argon;
[0085] Among them, the coating thickness is 1.4mm;
[0086] (4) sandblasting the target shaft workpiece obtained in step (3) according to the designed dimensions on a machine tool.
[0087] The performance data of the cladding layer of this embodiment are shown in Table 1.
[0088] Comparative Example 1
[0089] This comparative example provides a nickel-based alloy powder and a cladding layer.
[0090] The elemental composition of the nickel-based alloy powder provided in this comparative example comprises (based on the total mass of the nickel-based alloy powder as 100%): 7.5% W, 5% B, 6% Si, 23% Cr, 3.3% Nb, 35% Co, 1% La, 1.8% Hf, 0.08% impurities and the remainder Ni.
[0091] The nickel-based alloy powder provided in this comparative example is prepared by the following method:
[0092] (1) According to the elemental composition of the nickel-based alloy powder, 17 kg of raw materials Ni metal, 7.4 kg of W metal, 5.1 kg of B element, 6.1 kg of Si element, 23.1 kg of Cr element, 3.2 kg of Nb metal, 35.1 kg of Co metal, 1.1 kg of La metal and 1.9 kg of Hf metal were weighed for mixing; wherein the purity of Ni metal was 99.99 wt%, the purity of W metal was 99.96 wt%, the purity of B element was 99.5 wt%, the purity of Si element was 99.58 wt%, the purity of Cr element was 99.2 wt%, the purity of Nb metal was 99.92 wt%, the purity of Co metal was 99.95 wt%, the purity of La metal was 96.8 wt%, and the purity of Hf metal was 98 wt%;
[0093] (2) All raw materials are subjected to vacuum melting and gas atomization powder making, and then sieved (passed through an 80-mesh sieve and a 325-mesh sieve in sequence) to obtain a powder with a particle size of 45-180 μm, which is the nickel-based alloy powder provided in this comparative example; wherein, during the vacuum melting and gas atomization powder making process, the vacuum degree of vacuum melting does not exceed 10 Pa, the atmosphere of vacuum melting is an argon atmosphere, the temperature of vacuum melting is 1610° C., the pressure of gas atomization is 3.9 MPa, and the medium gas of gas atomization is argon.
[0094] In the above preparation method, the yield of powder with a particle size range of 45-180 μm is 69.3%; the particle size distribution of the prepared nickel-based alloy powder satisfies: particle size of 45-180 μm, D10 of 48.1 μm, D50 of 119.4 μm, D90 of 177 μm, fluidity of about 11.8 s / 50 g, microscopic particle sphericity of about 93.2%, oxygen content of about 69 ppm, and bulk density of 4.41 g / cm 3 , tap density 5.11g / cm 3 , there are hollow noodles (such as Figure 3 shown).
[0095] The cladding layer provided in this comparative example is prepared by the following method:
[0096] (1) The nickel-based alloy powder provided in this comparative example was sieved (passed through an 80-mesh sieve and a 325-mesh sieve in sequence to obtain a nickel-based alloy powder with a particle size of 45-180 μm) and dried (dried at 115° C. for 1.8 h under a vacuum degree of 14 Pa) to obtain a pretreated nickel-based alloy powder;
[0097] (2) The oxide layer and stains on the surface of the target shaft workpiece are removed by lathe processing. The size of the target shaft workpiece is 50 mm in diameter and 100 mm in length. The cladding area of the target shaft workpiece is 0.253 m 2 ;
[0098] (3) using the pretreated nickel-based alloy powder obtained in step (1), and adopting a laser cladding 3D printing method to prepare a cladding layer on the surface of the target shaft workpiece treated in step (2);
[0099] Among them, the laser used in laser cladding 3D printing is a semiconductor laser, and the laser cladding process parameters are: laser power 2500W, spot diameter 1.0mm, scanning line speed 30m / min, vacuum degree of vacuum environment ≤0.1pa, powder feeding rate 35g / min, working gas is argon;
[0100] Among them, the coating thickness is 2.1mm;
[0101] (4) sandblasting the target shaft workpiece obtained in step (3) according to the designed dimensions on a machine tool.
[0102] The performance data of the cladding layer of this comparative example are shown in Table 1.
[0103] Comparative Example 2
[0104] This comparative example provides a nickel-based alloy powder and a cladding layer.
[0105] The elemental composition of the nickel-based alloy powder provided in this comparative example comprises (based on the total mass of the nickel-based alloy powder as 100%): 6.7% W, 3.5% B, 6.3% Si, 19% Cr, 2.7% Nb, 31% Co, 0.5% La, 1.4% Hf, 0.026% impurities and the remainder Ni.
[0106] The nickel-based alloy powder provided in this comparative example is prepared by the following method:
[0107] (1) According to the elemental composition of the nickel-based alloy powder, 11.4 kg of raw materials Ni metal, 6.6 kg of W metal, 3.6 kg of B element, 6.4 kg of Si element, 19.1 kg of Cr element, 2.6 kg of Nb metal, 31.1 kg of Co metal, 0.7 kg of La metal and 1.5 kg of Hf metal were weighed for mixing; wherein the purity of Ni metal was 99.99 wt%, the purity of W metal was 99.96 wt%, the purity of B element was 99.5 wt%, the purity of Si element was 99.58 wt%, the purity of Cr element was 99.2 wt%, the purity of Nb metal was 99.92 wt%, the purity of Co metal was 99.95 wt%, the purity of La metal was 96.8 wt%, and the purity of Hf metal was 98 wt%;
[0108] (2) All raw materials are subjected to vacuum melting and gas atomization powder making, and then sieved (passed through an 80-mesh sieve and a 325-mesh sieve in sequence) to obtain a powder with a particle size of 45-180 μm, which is the nickel-based alloy powder provided in this comparative example; wherein, during the vacuum melting and gas atomization powder making process, the vacuum degree of vacuum melting does not exceed 10 Pa, the atmosphere of vacuum melting is an argon atmosphere, the temperature of vacuum melting is 1705° C., the pressure of gas atomization is 6.2 MPa, and the medium gas of gas atomization is argon.
[0109] In the above preparation method, the yield of powder with a particle size range of 45-180 μm is 66.3%; the particle size distribution of the prepared nickel-based alloy powder satisfies: particle size of 45-180 μm, D10 of 47.9 μm, D50 of 111.2 μm, D90 of 179 μm, fluidity of about 11.4 s / 50 g, microscopic particle sphericity of about 90.2%, oxygen content of about 101 ppm, and bulk density of 4.13 g / cm 3 , tap density 5.01g / cm 3 , there is macaroni.
[0110] The cladding layer provided in this comparative example is prepared by the following method:
[0111] (1) The nickel-based alloy powder provided in this comparative example was sieved (passed through an 80-mesh sieve and a 325-mesh sieve in sequence to obtain a nickel-based alloy powder with a particle size of 45-180 μm) and dried (dried at 115° C. for 1.8 h under a vacuum degree of 14 Pa) to obtain a pretreated nickel-based alloy powder;
[0112] (2) The oxide layer and stains on the surface of the target shaft workpiece are removed by lathe processing. The size of the target shaft workpiece is 50 mm in diameter and 100 mm in length. The cladding area of the target shaft workpiece is 0.253 m 2 ;
[0113] (3) using the pretreated nickel-based alloy powder obtained in step (1), and adopting a laser cladding 3D printing method to prepare a cladding layer on the surface of the target shaft workpiece treated in step (2);
[0114] Among them, the laser used in laser cladding 3D printing is a semiconductor laser, and the laser cladding process parameters are: laser power 2500W, spot diameter 1.0mm, scanning line speed 30m / min, vacuum degree of vacuum environment ≤0.1pa, powder feeding rate 35g / min, working gas is argon;
[0115] Among them, the coating thickness is 0.9mm;
[0116] (4) sandblasting the target shaft workpiece obtained in step (3) according to the designed dimensions on a machine tool.
[0117] The performance data of the cladding layer of this comparative example are shown in Table 1.
[0118] Comparative Example 3
[0119] This comparative example provides a nickel-based alloy powder and a cladding layer.
[0120] The elemental composition of the nickel-based alloy powder provided in this comparative example comprises (based on the total mass of the nickel-based alloy powder as 100%): 6.48% W, 5.05% B, 5.9% Si, 20.2% Cr, 2.55% Nb, 34.1% Fe, 1% La, 1.8% Hf, 0.026% impurities and the remainder Ni.
[0121] The nickel-based alloy powder provided in this comparative example is prepared by the following method:
[0122] (1) According to the elemental composition of the nickel-based alloy powder, 22.3 kg of raw materials Ni metal, 6.6 kg of W metal, 5.1 kg of B element, 6.1 kg of Si element, 20.1 kg of Cr element, 2.6 kg of Nb metal, 34.2 kg of Fe metal, 1.1 kg of La metal and 1.9 kg of Hf metal were weighed for mixing; wherein the purity of Ni metal was 99.99 wt%, the purity of W metal was 99.96 wt%, the purity of B element was 99.5 wt%, the purity of Si element was 99.58 wt%, the purity of Cr element was 99.2 wt%, the purity of Nb metal was 99.92 wt%, the purity of Co metal was 99.95 wt%, the purity of La metal was 96.8 wt%, and the purity of Hf metal was 98 wt%;
[0123] (2) All raw materials are subjected to vacuum melting and gas atomization powder making, and then sieved (passed through an 80-mesh sieve and a 325-mesh sieve in sequence) to obtain a powder with a particle size of 45-180 μm, which is the nickel-based alloy powder provided in this comparative example; wherein, during the vacuum melting and gas atomization powder making process, the vacuum degree of vacuum melting does not exceed 10 Pa, the atmosphere of vacuum melting is an argon atmosphere, the temperature of vacuum melting is 1651° C., the pressure of gas atomization is 4.6 MPa, and the medium gas of gas atomization is argon.
[0124] In the above preparation method, the yield of powder with a particle size range of 45-180 μm is 4.2%; the particle size distribution of the prepared nickel-based alloy powder satisfies: particle size of 45-180 μm, D10 of 46.3 μm, D50 of 114.5 μm, D90 of 171.1 μm, fluidity of about 11.3 s / 50 g, microscopic particle sphericity of about 91.3%, oxygen content of about 139 ppm, and bulk density of 4.21 g / cm 3 , tap density 5.16g / cm 3 , there is macaroni.
[0125] The cladding layer provided in this comparative example is prepared by the following method:
[0126] (1) The nickel-based alloy powder provided in this comparative example was sieved (passed through an 80-mesh sieve and a 325-mesh sieve in sequence to obtain a nickel-based alloy powder with a particle size of 45-180 μm) and dried (dried at 110° C. for 1.5 h under a vacuum degree of 15 Pa) to obtain a pretreated nickel-based alloy powder;
[0127] (2) The oxide layer and stains on the surface of the target shaft workpiece are removed by lathe processing. The size of the target shaft workpiece is 50 mm in diameter and 100 mm in length. The cladding area of the target shaft workpiece is 0.253 m 2 ;
[0128] (3) using the pretreated nickel-based alloy powder obtained in step (1), and adopting a laser cladding 3D printing method to prepare a cladding layer on the surface of the target shaft workpiece treated in step (2);
[0129] Among them, the laser used in laser cladding 3D printing is a semiconductor laser, and the laser cladding process parameters are: laser power 2500W, spot diameter 1.0mm, scanning line speed 30m / min, vacuum degree of vacuum environment ≤0.1pa, powder feeding rate 35g / min, working gas is argon;
[0130] Among them, the coating thickness is 1.1mm;
[0131] (4) The target shaft workpiece obtained in step (3) is finally sandblasted on a machine tool according to the designed dimensions.
[0132] The performance data of the cladding layer of this comparative example are shown in Table 1.
[0133] Table 1
[0134]
[0135]
[0136] From Table 1 and Figure 1 , Figure 2 It can be seen that the powder feeding conditions of the nickel-based alloy powder provided by the present invention are all good, there are no large numbers of irregularly shaped powder particles, the microscopic morphology of the nickel-based alloy powder is mainly regular spherical, with a small amount of rod-like structure, dry appearance quality, no obvious oxidized color particles, no visually visible inclusions, smooth surface, uniform particle size distribution, low impurity content and other performance characteristics.
[0137] The nickel-based alloy powder provided in Example 1 and Example 2 (the element content satisfies: 6-7% W, 4-8% B, 5-7% Si, 18-22% Cr, 2-3% Nb, 32-36% Co, 0.8-1.2% La, 1.5-2% Hf, ≤0.1% impurities and the remainder Ni), the cladding layer obtained at a scanning line speed of 30m / min has excellent performance and good hardness and quality of the cladding layer. The cladding layer prepared from the nickel-based alloy powders provided in Comparative Examples 1 and 2 (the element contents do not satisfy: 6-7% W, 4-8% B, 5-7% Si, 18-22% Cr, 2-3% Nb, 32-36% Co, 0.8-1.2% La, 1.5-2% Hf, ≤0.1% impurities and the remainder Ni) has performance significantly inferior to that of the cladding layer prepared from the nickel-based alloy powders provided in Example 1 and Example 2. The cladding layer prepared from the nickel-based alloy powder provided in Comparative Example 1 has poor wear resistance, low hardness, and small cracks in the cladding layer. The cladding layer prepared from the nickel-based alloy powder provided in Comparative Example 2 has average hardness, and small cracks in the cladding layer. The nickel-based alloy powder provided in Comparative Example 3 has different element types, and its oxygen content is significantly higher than that of the nickel-based alloy powder provided in Example 1 and Example 2. Its fluidity and sphericity are significantly lower than those of the nickel-based alloy powder provided in Example 1 and Example 2. The performance of the cladding layer prepared from the nickel-based alloy powder provided in Comparative Example 3 is significantly lower than that of the cladding layer prepared from the nickel-based alloy powder provided in Example 1 and Example 2. The hardness of the cladding layer prepared from the nickel-based alloy powder provided in Comparative Example 3 is average, and the cladding layer has large cracks.
[0138] The embodiments described above are for better explaining the present invention. For technical researchers in the field, it is not difficult to make various modifications to these embodiments without departing from the principles and spirit of the present invention. Therefore, the present invention is not limited to the embodiments herein. The improvements and changes made by those skilled in the art to the present invention according to the principles and spirit of the present invention should be within the protection scope of the present invention.
Claims
1. A nickel-based alloy powder, characterized in that: Taking the total mass of the nickel-based alloy powder as 100%, the element composition of the nickel-based alloy powder comprises: 6-7% W, 4-8% B, 5-7% Si, 18-22% Cr, 2-3% Nb, 32-36% Co, 0.8-1.2% La, 1.5-2% Hf, ≤0.1% impurities and the balance Ni; The nickel-based alloy powder has a particle size of 45-180 μm, fluidity ≤12s / 50g, microscopic particle sphericity ≥95%, oxygen content ≤80ppm, and bulk density ≥4.60g / cm 3 , tap density ≥5.30g / cm 3 .
2. The nickel-based alloy powder according to claim 1, characterized in that The particle size distribution of the nickel-based alloy powder satisfies: D10 is 40-50 μm, the particle size distribution of the nickel-based alloy powder satisfies D50 of 110-120 μm, and the particle size distribution of the nickel-based alloy powder satisfies D90 of 170-180 μm.
3. The nickel-based alloy powder according to claim 1, characterized in that Taking the total mass of the nickel-based alloy powder as 100%, the mass content of the hollow powder in the nickel-based alloy powder does not exceed 1%.
4. A method for preparing nickel-based alloy powder, characterized in that: The nickel-based alloy powder is the nickel-based alloy powder according to any one of claims 1 to 3, and the preparation method comprises: According to the element composition of the nickel-based alloy powder, the raw materials of Ni, W, B, Si, Cr, Nb, Co, La and Hf are weighed and mixed; All raw materials are vacuum melted and gas atomized to make powder, and then sieved to obtain the nickel-based alloy powder; Among them, in the vacuum melting and gas atomization powder making process, the vacuum degree of vacuum melting does not exceed 10Pa, the pressure of gas atomization is 4-6MPa, and vacuum melting and gas atomization are carried out under a protective gas atmosphere.
5. The method for preparing nickel-based alloy powder according to claim 4, characterized in that: The raw materials of Ni, W, B, Si, Cr, Nb, Co, La and Hf include Ni metal, W metal, B element, Si element, Nb metal, Co metal, La metal and Hf metal.
6. The method for preparing nickel-based alloy powder according to claim 4, characterized in that: During the vacuum melting gas atomization powder making process, the vacuum melting atmosphere is an inert gas atmosphere; In the process of vacuum melting gas atomization powder making, the atomization medium gas is argon.
7. The method for preparing nickel-based alloy powder according to claim 4, characterized in that: During the vacuum melting gas atomization powder making process, the vacuum melting temperature is 1620-1690℃.
8. A method for preparing a cladding layer, characterized in that: The method includes: Using the nickel-based alloy powder described in any one of claims 1 to 3 as a raw material, a cladding layer is prepared on the surface of a workpiece by a laser cladding 3D printing method; Among them, the laser cladding parameters are: laser power 2300-2600W, spot diameter 0.8-1.2mm, scanning line speed 26-32m / min, vacuum degree of vacuum environment ≤0.1pa, powder feeding rate 32-38g / min; Among them, the thickness of the cladding layer does not exceed 2mm.
9. The method for preparing the cladding layer according to claim 8, characterized in that: The working gas used in laser cladding is argon; The thickness of the cladding layer is 1-2mm.
10. A cladding layer, characterized in that: The cladding layer is prepared by the preparation method of the cladding layer according to claim 8 or 9, and the hardness of the cladding layer is 50HRC-55HRC.